HERBAL MEDICINES: OVERALL SATISFACTION AND MALAYSIA - Hamid, Junainah Abd; AK, Sairah (International Journal of Psychosocial Rehabilitation, 2020)
This study investigated the relation between attitude, branding as independent variable and overall customer satisfaction as dependent variables which contains of a number of factors towards herbal medicine among women Malaysian context. The study will enumerate the link amid dependent and independent factors. Such explorative nature investigation and came to conclusion about the significant association amid attitude, branding dependent factors and overall customer satisfaction independent factor. Investigator received a response rate of 82%. All the hypotheses of the studies are accepted. This investigation will provide the new insights to herbal manufacturing industry.Keywords---, , , overall customer satisfaction, Malaysia